Development Of Extruded Food Snack Using Modified Cassava Flour (Mocaf) With Addition Of Local Herbs - Mokhtar, Muhammad Wirawan Mohd (Universiti Sains Malaysia, 2020)
The aim of this study is to make a comprehensive review on the development of extruded snacks which involved the review on current research development on extruded snacks, the application of modified cassava flour (MOCAF) in food formulation and the utilisation of selected herbs and spices in food application. Cassava roots are known to have a high durability characteristics, albeit easily perishable and contain high cyanide content. The simplest way to tackle this problem is by processing the cassava roots into Modified Cassava Flour (MOCAF) as to reduce the moisture content and to remove the cyanide content. The MOCAF processing steps involved peeling of the root’s skin, fermentation, drying and milling. MOCAF portrays some similar characteristics to wheat flour, except it is a gluten-free. This similarities rise up an idea of substitution to MOCAF as the base ingredients in extruded snack food formulation. However, development of MOCAF-based extruded snack alone may perceived as an unhealthy food as it is low in some important nutrients such as vitamins and minerals.